"The labels don't work very well": Transgender individuals' conceptualizations of sexual orientation and sexual identity. Issue 2 (2nd April 2016) - Galupo, M. Paz; Henise, Shane B.; Mercer, Nicholas L.
ABSTRACT: The conceptualization and measurement of sexual orientation for transgender individuals is uniquely complicated by the way sexual orientation is rooted in dichotomous notions of sex and gender. The present research investigates the conceptualization of sexual orientation among transgender individuals by exploring the sexual identity labels they choose, the descriptions they provide for these labels, and their general descriptions of their sexuality. Participants included 172 adult U.S. residents, ranging in age from 18 to 65, who self-identified as transgender, transsexual, gender variant, or having a transgender history. Participants individually completed an online survey. Qualitative responses were analyzed via thematic analysis. Six themes were identified related to transgender individuals' descriptions of their sexuality: (1) trans sexuality as complex; (2) shifts in trans sexuality; (3) focus on beloved; (4) relationship style and status; (5) sexuality, bondage & discipline / domination & submission / sadism & masochism (BDSM), and kink; and (6) separating sexual and romantic attraction. Discussion focuses on the ways that transgender individuals' descriptions of sexuality fall outside the traditional research frameworks that problematize transgender experience, conflate gender identity and sexual orientation, and inherently define transgender experience in both cisnormative and heteronormative terms.